FAKTOR-FAKTOR YANG MEMPENGARUHI KONDISI AWAL COLLABORATIVE GOVERNANCE DALAM PEMETAAN WILAYAH ADAT DI KABUPATEN SORONG SELATAN - Apriadi, Yohanes (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Factors Affecting Initial Conditions Of Collaborative Governance In The Mapping Of Traditional Territory In Sorong Selatan District. Mapping of traditional territory is a mapping method using spatial information that places communities as actors in mapping their territories, as well as being the determinants of planning for the development of their own territories. The purpose of mapping traditional territory in South Sorong Regency is for indigenous peoples to have data that can be used as a reference for planning and management of their traditional territory, assisting the government in identifying indigenous peoples communities and regional development plans, clarifying territorial boundaries to avoid frequent vertical and horizontal conflicts and opening up spaces for collaboration with various parties in the context of planning sustainable management of traditional territory. The mapping of indigenous territory in South Sorong involved the South Sorong Regional Government, the Tehit Indigenous People and the NGO Econusa and Indonesian Conservation. The results of research on the initial conditions of collaboration show that there is an imbalance in the resources owned by the parties, which have the opportunity to be converted into collaboration strengths. In this study it was also found that there were collective incentives and institutional incentives which were the motivation for achieving common goals and there were also experiences of cooperation and past conflicts between the parties.